English Bosman and Dutch Bosman: A Comparison of Texts - Dantzig, A. (University of Ghana, 1705)
What will follow in this and subsequent papers will constitute an extended gloss of the English translation of Willem Bosman's account of the Guinea coast. This translation was published in London in 1705 under the title A New and Accurate Description of the Coast of Guinea. .And was based on the 1703 Dutch edition published in Amsterdam. For the English translation I have used the edited reprint published in 1967, which was an identical copy of the 1705 edition. For the Dutch version I have used the 173.7 edition, also published in Amsterdam; this was in fact the last of a series of reprints of the 1709 second edition. This second edition contained numerous amendments and additions to the first (1703) edition, and these will be noted as they occur. In addition to including all the material in the Dutch edition which was omitted from the English translation," I have included all passages in which significant differences in tone or meaning occur. Throughout I have tried to retain the capitalization, italicization, and punctuation employed in the Dutch version-styles to which the English translation generally conformed. Citation is by page number, paragraph, and line number within paragraph, with the first paragraph presumed to begin in each case with the first line of a page. Thus, for example, P. 17 1/8 indicates that the gloss concerns the eighth line of the first paragraph on page 17 of the English translation. Shorter passages are arranged on a FOR. READ basis, while for longer passages only the Dutch original is included after SHOULD READ. It is believed that this will not result in any problem of comparison. Besides comparing the texts directly I have added explanatory notes where these seemed appropriate
Heritage Material
Keywords: Translation; Guinea coast; English Bosman; Dutch Bosman; Texts